Circulating Biomarkers in Arterial Aneurysms - Singh , Rohit Kumar; Hakim , Mohd Zeeshan; Khanna , Ajay K. (Current Progress in Medicine and Medical Research Vol. 9, 2023)
Arterial aneurysms are a serious medical condition associated with high morbidity and mortality. The degenerative disease process, primarily driven by atherosclerosis and age-related changes in blood vessel structure, leads to the localized dilation of arteries. This chapter focuses on the role of circulating biomarkers in predicting and managing arterial aneurysms, with a particular emphasis on peripheral and abdominal aortic aneurysms in the Indian population. The objective is to identify specific biomarkers that can be used to predict aneurysm rupture by analysing blood samples from patients. Matrix metalloproteinase-9 (MMP-9), plasma fibrinogen, D-dimer, interleukin-6 (IL-6), and C-reactive protein (CRP) are examined as potential biomarkers. The findings from our study could contribute to the development of improved diagnostic tools and treatment strategies for arterial aneurysms, ultimately enhancing patient outcomes and reducing the burden of this condition on public health.